Spatial distribution of food acquisition points and their association with the prevalence of childhood obesity in La Union County, Costa Rica - Reyes Chaves, Jonnathan (2020)
Introduction: Childhood obesity is a public health problem in Costa Rica and its prevalence has shown rapid growth. The food and physical activity environment plays a crucial role in the lifestyle of school-age children and their families. This article tries to understand how the spatial distribution of places of purchase and sale of food can influence the prevalence of childhood obesity in two schools in the canton of La Unión. Materials and methods: A mapping of the location of food sales places in the 8 districts, the presence of patents in them and the distances traveled by schoolchildren from the districts of San Juan and Concepción and their relationship with the nutritional status of 297 school children. Results: 338 food acquisition points located mainly in the Tres Ríos district were identified in very short distances from the educational centers. For the students of Concepción District, the distances traveled to school decrease significantly as the overweight in schoolchildren increases. Conclusions: There is a significant growth in the places of sale and distribution of food that are located at distances no greater than 250 meters from educational centers, which increases the probability of accessing the food that is sold there. As excess weight increases in schoolchildren, they report shorter distances traveled to school, which adds a greater risk in this population which adds a greater risk in this population associated with reduced physical activity